Altered thyroid hormone levels affect body condition at metamorphosis in larvae of Xenopus laevis. Issue 11 (30th July 2018) - Ruthsatz, Katharina; Dausmann, Kathrin H.; Drees, Claudia; Becker, Laura I.; Hartmann, Lisa; Reese, Janica; Sabatino, Nikita M.; Peck, Myron A.; Glos, Julian
Abstract: Chemical, physical and biological environmental stressors may affect the endocrine system, such as the thyroid hormone (TH) axis in larval amphibians with consequences for energy partitioning among development, growth and metabolism. We studied the effects of two TH level affecting compounds, exogenousl ‐thyroxine (T4 ) and sodium perchlorate (SP), on various measures of development and body condition in larvae of the African clawed frog ( Xenopus laevis ). We calculated the scaled mass index, hepatosomatic index and relative tail muscle mass as body condition indices to estimate fitness. Altered TH levels significantly altered the growth, development, survival and body condition in metamorphic larvae in different directions. While exogeno us T4 reduced growth and accelerated development, SP treatment increased growth but slowed down development. Altered TH levels improved body conditions in both treatments and particularly in larvae of the SP treatment but to the detriment of lower survival rates in both TH level altering treatments. The hepatosomatic index was negatively affected by exogenous T4, but not by SP treatment indicating a lower lipid reserve in the liver in larvae of T4 treatment. These altered TH levels as caused by several environmental stressors may have an influence on individual fitness across life, as body condition at the onset of metamorphosis determines metamorphic and juvenile survival. Further research is needed to determine synergetic effects of environmental stressors on TH levels and its effects on physiological traits such as metabolic rate. Abstract : We studied the effects of two model thyroid hormone level affecting compounds, l ‐thyroxine and sodium perchlorate, on various measures of development and body condition in larvae of the African clawed frog ( Xenopus laevis ). The scaled mass index, hepatosomatic index and the relative tail muscle mass were calculated as body condition indices to estimate fitness. Altered thyroid hormone levels reduced survival rate, altered growth and development and improved body condition of larvae at the onset of metamorphosis.